MODEL PENDIDIKAN KETELADANAN KEPEMIMPINAN: TANTANGAN PENGEMBANGAN SUMBER DAYA MANUSIA - Render Bin Luwis (Jurnal Excelsior Pendidikan, 2020)
Abstract:Â Theoretical basis: Education (pedagogy) means science that investigates, and reflects on, the symptoms of educating. Research Objectives: To answer the following questions: (1) What is meant by exemplary leadership education? (2) How is exemplary education in teaching unity with the church based as a role model in resource development? (3) What is the model for exemplary leadership education? Methods: The research method in this article is qualitative, while the data collection techniques use interviews and observations, while the data collection technique has a data analysis process using the Husserlin phenomenology approach. Results: (1) Leadership education based on Ephesians 4: 1-16 is a model of exemplary character, exemplary teaching in church unity, and exemplary in church maturity. (2) Exemplary education in teaching unity with the congregation is based as a role model in human resource development among God's servants in GBBM that can be emulated by the congregation is an example of the character of Jesus Christ who is the only Lord and Savior for all people, ) The leadership model of "character integrity", which boils down to centering on the faith and character of Christ, is transmitted to the servants of God and then the entire church congregation. Christ's "character integration" is the human resource among the servants of God and the entire church congregation is eternal, unlimited, which will produce success in life and all ministries in the church.Abstrak:Â Landasan Teori: Pendidikan (pedagogi) berarti ilmu pengetahuan yang menyelidiki, dan merenungkan tentang gejala-gejala mendidik. Tujuan Penelitian: Menjawab persoalan-persoalan sebagai berikut: (1) Apakah yang dimaksud dengan pendidikan keteladanan kepemimpinan? (2) Bagaimanakah pendidikan keteladanan dalam pengajaran kesatuan dengan jemaat berdasarkan sebagai Role Model dalam Pengembangan Sumber Daya? (3) Bagaimanakah model pendidikan keteladanan kepemimpinan? Metode: Metode penelitian dalam artikel ini adalah Kualitatif, sedangkan teknik pengumpulan data menggunakan wawancara dan observasi sedangkan teknik pengumpulan data mempunyai proses analisis data menggunakan pendekatan Fenomenologi Husserlin. Hasil: (1) Pendidikan kepemimpinan berdasarkan Efesus 4:1-16 adalah model keteladanan dalam karakter, keteladanan dalam pengajaran kesatuan jemaat, dan keteladanan dalam pendewasaan jemaat.Â  (2)Â  Pendidikan keteladananÂ  dalam pengajaran kesatuan dengan jemaat berdasarkan sebagai RoleÂ  ModelÂ  dalam Pengembangan Sumber DayaÂ  Manusia di antara para hamba Tuhan di GBBM yang dapat dicontoh oleh jemaat adalah teladan karakter Yesus Kristus yang merupakan satu-satunya Tuhan dan Juruselamat untuk semua orang, (3) Model kepemimpinan â€œintegritas karakterâ€, yang bermuara dari berpusat pada iaman dan karakter Kristus, tertular kepada para hamba TuhanÂ  dan kemudian seluruh jemaat gereja. â€œintegrase karakterâ€ Kristus adalah sumber daya manusia di natara para hamba Tuhan dan seluruh jemaat gereja bersifat kekal, tidak terbatas, yang akan membuahkan keberhasilan dalam hidup dan segala pelayanan dalam gereja.